EU's carbon border adjustment mechanism CBAM: Industrial effects - Brita Bye; Kevin R. Kaushal; Halvor Briseid Storrøsten (Statistics Norway, Research Department, 2024)
We examine the industrial effects of two measures aimed at mitigating carbon leakage: the EU's scheduled Carbon Border Adjustment Mechanism (CBAM) and the allocation of free emission allowances. Currently, the EU allocates free emission allowances based on output (known as outputbased allocation, or OBA) to emission-intensive and trade-exposed (EITE) sectors. This system is slated to be replaced by the CBAM, which imposes a tariff on imports of EITE goods and electricity into the EU. We analyze the effects of this transition, focusing on EU EITE industries. OBA boosts output in the EU's EITE sectors compared to a scenario without any anti-leakage policies. CBAM produces similar effects, except in the case of non-ferrous metals, where output declines. Beyond non-ferrous metals, the positive output effects of CBAM are modest for refined petroleum products and chemical products compared to OBA. Key factors influencing these differences include the sectors' initial emission intensities, export shares, and reliance on intermediate inputs. These factors may also explain why some sectors are resisting the shift from OBA to CBAM.
Keywords: D61; F18; H23; Q54; 330; Carbon leakage; carbon border adjustment mechanism; output-based allocation